DESIGNING A WEB-BASED TEACHER DATA INFORMATION SYSTEM AT PENRAUJAN JUNIOR HIGH SCHOOL USING THE LARAVEL FRAMEWORK - Simanullang, Nia Daniati; Abdul Khaliq; Afif Badawi (Bahasa Indonesia, 2026)
The development of information technology encourages educational institutions to utilize web-based information systems to support more effective and efficient administrative management. Penraujan Junior High School still faces obstacles in managing teacher data which is done manually or using simple applications, so that it has the potential to cause recording errors, data duplication, and difficulties in finding and compiling reports. This research aims to design and build a web-based teacher data information system at Penraujan Junior High School using the Laravel framework. The methods used in this study include system needs analysis, system design, and system implementation and testing. The system was developed using the PHP programming language with the Laravel framework and MySQL database. The result of this research is in the form of a teacher data information system that is able to manage teacher data in an integrated manner, facilitate the process of storing, searching, and processing data, and producing accurate and up-to-date information. With this system, it is hoped that the management of teacher data at Penraujan Junior High School can be carried out more optimally and support the improvement of school administrative performance.